Burden of invasive pneumococcal disease in children aged 1 month to 12 years living in South Asia: a systematic review. - Nishant Jaiswal; Meenu Singh; Kiran Kumar Thumburu; Bhavneet Bharti; Amit Agarwal; Ajay Kumar; Harpreet Kaur; Neelima Chadha (PLoS ONE)
Objective The primary objective was to estimate the burden of invasive pneumococcal disease (IPD) in children aged 1 month to 12 years in South Asian countries. Methods We searched three electronic databases (PubMed, Embase and the Cochrane Library) using a comprehensive search strategy, we manually searched published databases (Index Medicus and Current Contents) and we also searched the bibliographies of the included studies and retrieved reviews. The searches were current through June 2013. Eligible studies (community-based and hospital-based) were pooled and a separate analysis for India was also completed. A meta-regression analysis and heterogeneity analysis were performed. The protocol was registered with PROSPERO registration number CRD42013004483. Results A total of 22 studies surveying 36,714 children were included in the systematic review. Hospital-based prospective studies from South Asia showed that 3.57% of children had IPD, and 15% of all bacterial pneumonia cases were due to Streptococcus pneumoniae. Indian studies showed that the incidence of IPD was 10.58% in children admitted to hospitals with suspected invasive bacterial diseases, and 24% of all bacterial pneumonia cases were due to S. pneumonia. Population-based studies from South Asian countries showed that 12.8% of confirmed invasive bacterial diseases were caused by S. pneumonia whereas retrospective hospital-based studies showed that 28% of invasive bacterial diseases were due to S. pneumoniae. Meta-regression showed that there was a significant influence of the antigen testing method for diagnosing IPD on IPD prevalence. Conclusion S. pneumoniae is responsible for a substantial bacterial disease burden in children of South Asian countries including India despite the presence of high heterogeneity in this meta-analysis. Treatment guidelines must be formulated, and preventive measures like vaccines must also be considered.